2017
DOI: 10.1371/journal.pone.0175347
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the parapapillary atrophy zones in en face optical coherence tomography images

Abstract: ObjectiveTo measure the parapapillary atrophy (PPA) area in en face images obtained with swept-source optical coherence tomography (SS-OCT), and to evaluate its relationship to glaucoma, myopia, and age in non-highly myopic subjects.DesignRetrospective, cross-sectional study.ParticipantsFifty eyes of 30 subjects with open-angle glaucoma (G group) and forty-three eyes of 26 healthy control subjects (C group). Eyes with high myopia (spherical equivalent refractive error ≤ -8 diopters or axial length ≥ 26.5 mm) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
(65 reference statements)
1
28
0
1
Order By: Relevance
“…But previous investigations have also revealed that PPA +BM was more significantly correlated with glaucoma [1,2,4,43]. Teng et al [44] described that high IOP in patients with glaucoma may cause obstruction of the parapapillary choriocapillaris and, in turn, may lead to the degeneration of the RPE and adjacent cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…But previous investigations have also revealed that PPA +BM was more significantly correlated with glaucoma [1,2,4,43]. Teng et al [44] described that high IOP in patients with glaucoma may cause obstruction of the parapapillary choriocapillaris and, in turn, may lead to the degeneration of the RPE and adjacent cells.…”
Section: Discussionmentioning
confidence: 98%
“…In terms of β-zone PPA, PPA +BM has been reported to be associated with older age or myopia [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of β-zone PPA, PPA +BM has been reported to be associated with older age or myopia [3][4][5]. But previous investigations have also revealed that PPA +BM was more significantly correlated with glaucoma [1,2,4,43]. Teng et al [44] described that high IOP in patients with glaucoma may cause obstruction of the parapapillary choriocapillaris and, in turn, may lead to the degeneration of the RPE and adjacent cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinic-based studies have shown that PPA +BM was mostly associated with glaucoma, older age, and myopia. However, PPA -BM was associated with a longer axial length but not with glaucoma [2][3][4][5]. A previous study showed that optic nerve head (ONH) tilt was associated with PPA +BM and PPA -BM widths, which suggested that the microstructure of PPA might reflect the myopic remodeling of the ONH [6].…”
Section: Introductionmentioning
confidence: 96%